2011
DOI: 10.1007/dcr.0b013e3182093c68
|View full text |Cite
|
Sign up to set email alerts
|

Single-Access Laparoscopic Low Anterior Resection With Vertical Suspension of the Rectum

Abstract: Low anterior single-access laparoscopic resection seems safe and feasible when the rectum is suspended like a swing to ensure an adequate operative field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In single-access laparoscopic surgery, the first report from Hamzaoglu et al [9] shows promising preliminary pathologic results in 4 cases of LAR with the introduction of a sutured sigmoid hung into the abdominal wall as a way of attaining adequate exposure for TME. In 2010, Uematsu et al [18] reported a novel single-access port for use in a sigmoidectomy, and in 2011 there was a report of the use of a suspending bar to lift up the sigmoid for TME [10] with excellent pathologic results. Another 2 reports [11, 12] also showed good pathologic results (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…In single-access laparoscopic surgery, the first report from Hamzaoglu et al [9] shows promising preliminary pathologic results in 4 cases of LAR with the introduction of a sutured sigmoid hung into the abdominal wall as a way of attaining adequate exposure for TME. In 2010, Uematsu et al [18] reported a novel single-access port for use in a sigmoidectomy, and in 2011 there was a report of the use of a suspending bar to lift up the sigmoid for TME [10] with excellent pathologic results. Another 2 reports [11, 12] also showed good pathologic results (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to SALS rectal procedures, the first report presented by Hamzaoglu et al showed excellent results (18), although there were some deficiencies in terms of instrument collision, excessive traction on the rectum for pelvic dissection, and restricted video laparoscopic view. Some later reports presented a modified technique that solved these problems in SALS for rectal cancer surgery with acceptable oncologic results (5,6,(19)(20)(21)(22). The one difficult point in SALS is determining how to apply the endo-stapler; the options are as follows: (i) add one more port for ileostomy creation or drain placement (19); (ii) the prolapsing technique (23,24); and (iii) add another port in a multichannel port.…”
Section: Single and Conventional Laparoscopic In Rectum S Sirikurnpiboonmentioning
confidence: 99%
“…The fairly great distance of the spleen and the deep pelvis from the umbilicus amplify the difficulty of creating instrument triangulation, especially when standard, straight laparoscopic instruments are used. Even adequate traction of the rectum and stapling procedures have been associated with technical difficulties and adjunctive methods of traction and suspension such as transparietal suture, are frequently needed to achieve adequate surgical exposure [51][52][53][54][55][56]. Bulut et al [57] have recently reported their early experience in singleincision surgery for rectal cancer treatment.…”
Section: Feasibility and Safety Of Single-incision Colectomymentioning
confidence: 99%
“…Uematsu et al [54] have proposed a new rectumsuspending system composed of a suspending bar and a bowel clamp with an extracorporeal magnetic tool. This apparatus, along with single access through the right iliac fossa instead of the umbilicus, allowed the authors to perform TME and transect the rectum by ensuring a proper tension.…”
Section: Feasibility and Safety Of Single-incision Colectomymentioning
confidence: 99%